2008
DOI: 10.1183/09031936.00125707
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in end-stage COPD

Abstract: Although feelings of anxiety and depression are common in patients with chronic obstructive pulmonary disease (COPD), estimates of their prevalence vary considerably. This probably reflects the variety of scales and methods used to measure such symptoms. Regardless of whether anxiety and depression are considered separately or as a single construct, their impact on COPD patients is important.A heightened experience of dyspnoea is likely to be a contributing factor to anxiety. Feelings of depression may be prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
147
0
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(162 citation statements)
references
References 127 publications
(169 reference statements)
3
147
0
12
Order By: Relevance
“…They may feel useless, experience reduced sexual activity, depend on others for their personal care, and lose interest in future projects. 38 Tobacco may provide psychological relief for some individuals. 39 Continuing smokers with COPD are more at risk of depression than those who quit.…”
Section: Discussionmentioning
confidence: 99%
“…They may feel useless, experience reduced sexual activity, depend on others for their personal care, and lose interest in future projects. 38 Tobacco may provide psychological relief for some individuals. 39 Continuing smokers with COPD are more at risk of depression than those who quit.…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms that are clinically relevant are estimated to occur in 10-80% of all patients. Conversely, in clinically stable outpatients with COPD, the prevalence of major depression (that requires medical intervention) ranges 19-42% [132,133]. There is no standardised approach for the diagnosis of depression in patients with COPD because of the differences in methodology and variability of the screening questionnaires in cut-off points to determine a diagnosis of depression.…”
Section: Depressionmentioning
confidence: 99%
“…Whatever the cause, untreated depression increases the length of hospital stay, frequency of hospital admissions, and leads to impaired quality of life and premature death [133]. However, depression often remains untreated in COPD patients.…”
Section: Treatmentmentioning
confidence: 99%
“…Experience of severe shortness of breath is likely to contribute anxiety whereas loss and grief related with the disability due to COPD may lead to depression 2 . Studies have even suggested that the presence of shortness of breath and exacerbation of symptoms contributes to depression, which is the most important determinant to impair health related quality of life 3 .…”
Section: Introductionmentioning
confidence: 99%